Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Which of the following equations is equivalent to 3(2p + 4) – (3p – 4) = 43?
Group of answer choices

2p + 8 = 43

3p + 8 = 43

2p + 16 = 43

3p + 16 = 43


Sagot :

I just solved it for you and the answer i got was D